2002
DOI: 10.1093/jn/132.6.1194
|View full text |Cite
|
Sign up to set email alerts
|

The Seeds from Plantago ovata Lower Plasma Lipids by Altering Hepatic and Bile Acid Metabolism in Guinea Pigs

Abstract: Psyllium, the husks from Plantago ovata (PO), is recognized as a potent agent in lowering plasma cholesterol. In this study, we tested the potential hypolipidemic effects of the seeds from PO and the mechanisms associated with the lowering of plasma lipids. Male Hartley guinea pigs (n = 30; 10 per group) were fed either a control diet or diets containing 7.5 or 10 g/100 g PO for 4 wk. Diets were identical in composition except for the fiber source. The control diet contained 10 g/100 g cellulose and 2.5 g/100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 41 publications
3
36
0
Order By: Relevance
“…But maybe in long term treatment there would be positive change for them, because as other studies showed cucurbita pepo species can effect lipid profile and even other blood factors.Fibers reduce plasma LDL level by inhibiting the absorbtion of cholesterol and bile acids and improving the activity of LDL receptors, so it could be concluded that pumpkin reduces the effect of lipids through its fibers. Fiber can also reduce triglyceride levels by suppressin lipogenesis in the liver 19,20 .The lipidreducing properties of cucurbita pepo plant are partly attributed to the pectin present on it. Pectin enhances the activity of lipoprotein lipase in fat tissue and heart, resulting in higher absorption of triglyceride rich lipoproteins (VLDL and chylomicron) in tissues other than liver to promote their breakdown and therefore reducing triglyceride levels Previous data suggest that diets rich in pectin facilitate excretion of bile acids which lead to their synthesis increase from cholesterol All the Results are set in a table1.…”
Section: Results: Discussionmentioning
confidence: 99%
“…But maybe in long term treatment there would be positive change for them, because as other studies showed cucurbita pepo species can effect lipid profile and even other blood factors.Fibers reduce plasma LDL level by inhibiting the absorbtion of cholesterol and bile acids and improving the activity of LDL receptors, so it could be concluded that pumpkin reduces the effect of lipids through its fibers. Fiber can also reduce triglyceride levels by suppressin lipogenesis in the liver 19,20 .The lipidreducing properties of cucurbita pepo plant are partly attributed to the pectin present on it. Pectin enhances the activity of lipoprotein lipase in fat tissue and heart, resulting in higher absorption of triglyceride rich lipoproteins (VLDL and chylomicron) in tissues other than liver to promote their breakdown and therefore reducing triglyceride levels Previous data suggest that diets rich in pectin facilitate excretion of bile acids which lead to their synthesis increase from cholesterol All the Results are set in a table1.…”
Section: Results: Discussionmentioning
confidence: 99%
“…The plasma cholesterol-lowering properties of DF such as b-glucan, psyllium (Romero et al 2002), guar gum (Fernandez et al 1995;Seal & Mathers, 2001), pectin (Fernandez et al 1994), algal polysaccharides (Dvir et al 2000;Seal & Mathers, 2001) or special DF sources such as rhubarb stalk fibre (Goel et al 1999) seem to be mostly related to their macromolecular state. The plasma cholesterol-lowering effects are found especially in hypercholesterolaemic human subjects or animals, and are connected directly or indirectly with the metabolism of bile acids (BA) and neutral sterols (NS) in the intestinal tract and liver.…”
mentioning
confidence: 99%
“…Normally, psyllium is cultured for its mucilage content, which is a white fibrous material with hydrophilic characteristic. The mucilage can be obtained by mechanical milling/grinding, and is usually referred to as husk [7]. Psyllium is the commonly used word for more than 200 species of the plant genus Plantago which are used commercial manufacturing of mucilage.…”
Section: Introductionmentioning
confidence: 99%